Krasnyi kvadrat . Krasnyi kvadrat . Red Square Box . Красный квадрат - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The debate on the political situation in Georgia. Featured in the program: Shevardnadze, Eduard Amvrosievich (Chairman of the State Council of Georgia); Fedorov, Andrei (Advisor to the Vice-President of the Russian Federation); Aleksidze, Levan (Chairman of the State Council of Foreign Affairs of Georgia); Achba, Zurab (Deputy Chairman of the Parliamentary Commission for Legal Affairs of Abkhazia); Migranian, Andranik Movsesovich (Political Scientist) Contributors: Liubimov, Aleksandr Mikhailovich (Anchor) Дискуссия о политической обстановке в Грузии. В программе участвуют: Шеварднадзе, Эдуард Амвросиевич (Председатель Государственного Совета Грузии); Федоров, Андрей (Советник вице-президента Российской Федерации); Алексидзе, Леван (Председатель Комиссии по международным делам госсовета Грузии); Ачба, Зураб (Заместитель председателя комиссии парламента Абхазии по правовым вопросам); Мигранян, Андраник Мовсесович (Политолог) Создатели: Любимов, Александр Михайлович (Ведущий/Ведущая)